Do púlpito aos lares: o jornal Até quê... da Diocese de Palmas-Francisco Beltrão no episcopado de Dom Agostinho - Pongan, Pâmela (2023)
In the Southwest region of Paraná, for 28 years, a religious newspaper, "Até que..." (1985 - 2013), designed and organized by the second bishop of the Diocese of Palmas - Francisco Beltrão, Dom Agostinho José Santori, with distribution monthly throughout the diocesan territory. Thus, his first measures were oriented and influenced by the Second Vatican Council and the Brazilian Military Dictatorship, which resulted in resistance from conservative parts of the Church, mainly due to their inclination towards Theology of Liberation. Thus, the present research aims to analyze the discourses present in this newspaper produced by the Diocese, linked to the Catholic Church, in its political aspects, economic and social, at the same time that it seeks to understand, with the use of methodologies of Content Analysis, by Laurence Bardin and Discourse Analysis, by Patrick Charaudeau, how the media constructs and reproduces this discourse as true, based on the principles religious, by acting as a reference beyond the earthly field, presenting themselves as materialization of divine desires and teachings, passing through discourse, between divine and earthly fields, to structure and maintain itself as a source of information, at the same time time that propagates ideas and values ​​with purposes linked to the institution and its administrator. The choice of this theme considered the relationship between politics and the religious sphere, where we sought understand how the Church - in the figure of Dom Agostinho - used its printed media to transmit its political side and social ideas, seeking to maintain its hegemony in the region southwest, based on Christian values ​​and dogmas, considering its wide circulation. Through the analysis of these sources, we will be able to understand and reflect on how this printed material presented regional, national, religious issues, and, mainly, the opinion expressed of the diocesan bishop. In this way, the use of printed materials as signs of presence was dentified of the diocesan Church in the region, being the means by which the positions of the Church and the bishop, seeking to influence the thinking and behavior of readers. Consolidating, Thus, the power of the Diocesan Church, as a guide for its faithful, being lose to the be in all communities and homes in the region, while reinforcing the figure of Dom Agostinho as a regional political agent.